Role of TNF-α and FGF-2 in the Fracture Healing Disorder of Type 2 Diabetes Model Induced by High Fat Diet Followed by Streptozotocin - Huang H (Dove Medical Press, 2020)
Heqing Huang, Ling Luo, Zhitao Liu, Yan Li, Zhaochen Tong, Zhendong Liu Department of Orthopaedics and Traumatology, Third Xiangya Hospital of Central South University, Changsha 410013, Hunan Province, People’s Republic of ChinaCorrespondence: Zhendong LiuDepartment of Orthopaedics and Traumatology, Third Xiangya Hospital of Central South University, No. 138 Tongzipo Road, Changsha 410013, Hunan Province, People’s Republic of ChinaTel/Fax +8673188638888Email liuzhendong001@163.comPurpose: To investigate the effect of TNF-α and FGF-2 in the fracture healing disorder of type 2 diabetes.Design/Methodology/Approach: Rat diabetes-bone traction model was established to investigate the effect of type 2 diabetes on the fracture healing and the association of TNF-α and FGF-2 with the process. Serological examination was performed to detect the related diabetes indexes. The proliferation activity of the cells was detected by MTT assay. The expressions of FGF-2 and TNF-α of osteoblasts in high glucose culture environment were detected by histochemistry and Western blotting.Findings: Serological examination showed that in rats fed with high fat and sugar diet for 8 weeks, the serum total cholesterol (TC), triglyceride (TG), fasting insulin (FINs) significantly increased, but fasting blood glucose (FBG) had no significant change. Two weeks after intraperitoneal injection of STZ, rat serum TG, TC, and FBG increased significantly, while FINs did not change obviously. Two weeks after traction osteogenesis, X-ray examination and HE staining showed that the area of osteotylus in the diabetes group was significantly smaller than that in the control group. The number of PCNA positive cells in the osteotylus of diabetes group was significantly decreased. In the osteotylus of diabetes group, the expression of TNF-α was significantly increased and the expression of FGF-2 was significantly decreased. MTT assay showed that the proliferation activity of MC3T3-E1 cells in high glucose culture medium groups was significantly decreased at 24th hour of the culture, compared with the normal culture medium group. qPCR results showed that the expression of FGF-2 was significantly decreased while the expression of TNF-α was significantly increased in high glucose culture medium groups.Originality/Value: It was concluded that type 2 diabetes mellitus affected the fracture healing by causing osteoblast proliferation disorder. TNF-α and FGF-2 were important related factors for the process.Keywords: type 2 diabetes mellitus, T2DM rat model, distraction osteogenesis, fracture healing, FGF-2, TNF-α, MC3T3-E1 cells